Real-time cooling power attribution for co-located data center rooms with distinct temperatures and humidities - Wang, Rongrong (2022)
At present, a co-location data center often applies an identical and low temperature setpoint for its all server rooms. Although increasing the temperature setpoint is a rule-of-thumb approach to reducing the cooling energy usage, the tenants may have different mentalities and technical constraints in accepting higher temperature setpoints. Thus, supporting distinct temperature setpoints is desirable for a co-location data center in pursuing higher energy efficiency. This calls for a new cooling power attribution scheme to address the inter-room heat transfers that can be up to 9% of server load as shown in our real experiments. This article describes our approaches to estimating the inter-room heat transfers, using the estimates to rectify the metered power usages of the rooms' air handling units, and fairly attributing the power usage of the shared cooling infrastructure (i.e., chiller and cooling tower) to server rooms by following the Shapley value principle. Extensive numeric experiments based on a widely accepted cooling system model are conducted to evaluate the effectiveness of the proposed cooling power attribution scheme. A case study suggests that the proposed scheme incentivizes rational tenants to adopt their highest acceptable temperature setpoints under a non-cooperative game setting. Further analysis considering distinct relative humidity setpoints shows that our proposed scheme also properly and inherently addresses the attribution of humidity control power.